2017
DOI: 10.1111/jphd.12260
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between fluoride intake levels and fluorosis of late‐erupting permanent teeth

Abstract: Our results clearly show that dental fluorosis prevalence is closely related to fluoride intake levels and that teeth have greater susceptibility to fluoride intake during certain age intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The available literature does not contain any studies concerning the correlation between prevalence of fluorosis and intake of fluorides from diet supplementation preparations and plant products. Similar conclusions were drawn by Bhagavatula et al [3], whereas Khandare and Rao [9] claim that water and food are the main sources of fluoride for the humans. Fluorine content in plants depends mostly on its concentration in the soil, chemical composition of the soil, especially the of amount of calcium and phosphorus, as well as the type of soil [10,49].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The available literature does not contain any studies concerning the correlation between prevalence of fluorosis and intake of fluorides from diet supplementation preparations and plant products. Similar conclusions were drawn by Bhagavatula et al [3], whereas Khandare and Rao [9] claim that water and food are the main sources of fluoride for the humans. Fluorine content in plants depends mostly on its concentration in the soil, chemical composition of the soil, especially the of amount of calcium and phosphorus, as well as the type of soil [10,49].…”
Section: Discussionsupporting
confidence: 82%
“…The highest average number of teeth affected by fluorosis in the examined group from Sosnilka was recorded in sextant II -3.52 and sextant V -1.30. Bhavagatula et al [3] proved that dental fluorosis was most frequently observed in upper incisors and least frequently in lower incisors. Studies by Sudhir [40] in Nalgonda, Andhra Pradesh District, south-east India, did not reveal any statistically significant differences between mandibular and maxillary incisor teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its presence is bilateral and symmetrical on the enamel (3), depending on the period of dental development in which contact occurred (4). It appears with lines in the form of horizontal striations, without a defined pattern (5), ranging from an opaque white (6) to the total loss of the enamel (7). Clinical variations are related to histological changes, cataloged with the TF index (8).…”
Section: Introductionmentioning
confidence: 99%
“…(Erdal and Buchanan, 2005) The chronic toxic effect of excessive intake of fluoride has also been documented to include skeletal fluorosis,neurological manifestations such as lowering of the intelligence quotient(IQ), gastrointestinal tract(GIT), dyspeptic symptoms and urinary tract malfunctioning. (Bhagavatula et al, 2018)These symptoms,unlike DF,have been noted mostly at higher concentrations of fluoride ranging from 2mg/l for low IQ in children,3.2mg/l for GIT symptoms, 8mg/l for renal symptoms and 10mg/l for crippling skeletal fluorosis. (Derryberry, Bartholomew and Fleming, 1963) Among all these ,DF is the most common unwanted effect of chronic exposure to fluoride and the importance of this condition is its role as the earliest indicator of excessive fluoride exposure in a population.…”
Section: Introductionmentioning
confidence: 99%